Pendampingan Tadarus Sebelum Belajar untuk Meningkatkan Nilai Spiritualitas Siswa SD Tahfidz Al-Jamiel Palangka Raya - Achmadi Achmadi; Syahmidi Syahmidi; Muhammad Athaillah (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The purpose of this mentoring is to increase the spiritual value that exists in students at SD Tahfidz Al-Jamiel Palangka Raya. Through the tadarus mentoring programme before the lesson starts. This service uses th e Asset Based Community Development (ABCD) method. Assistance is carried out by accompanying students when carrying out the Qur'an tadarus before the teacher enters the class. The results of this mentoring programme show that this mentoring is quite effective so that it can increase the spiritual value that exists in students and foster students' love of reading the Qur'an.